2021
DOI: 10.2147/jir.s303105
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Propionate Enhances Nrf2-Mediated Protective Defense Against Oxidative Stress and Inflammation in Lipopolysaccharide-Induced Neonatal Mice

Abstract: Background Alveolar arrest and the impaired angiogenesis caused by chronic inflammation and oxidative stress are two main factors in bronchopulmonary dysplasia (BPD). Short-chain fatty acids (SCFAs), especially propionate, possess anti-oxidant and anti-inflammatory effects. The present study was designed to examine the roles of sodium propionate (SP) on lipopolysaccharide (LPS)-challenged BPD and its potential mechanisms. Methods WT, Nrf2 -/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…For experiments with the SP treatment, maternal mice were administered SP (200 mmol L −1 , Sigma-Aldrich, USA) in the drinking water ad libitum at the termination of hypoxia exposure until 14 d postpartum while the control and IUGR dams still drank normally (n = 3 per group). 25,26 After 14 d postpartum, all dams drank normally until the end of lactation. Male offspring from dams were selected after postnatal day 21 (PN 21) and housed on a 12 h light/dark cycle in a temperature-controlled room with standard chow and tap water ad libitum.…”
Section: Maternal Hypoxia-induced Iugr Mouse Model and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For experiments with the SP treatment, maternal mice were administered SP (200 mmol L −1 , Sigma-Aldrich, USA) in the drinking water ad libitum at the termination of hypoxia exposure until 14 d postpartum while the control and IUGR dams still drank normally (n = 3 per group). 25,26 After 14 d postpartum, all dams drank normally until the end of lactation. Male offspring from dams were selected after postnatal day 21 (PN 21) and housed on a 12 h light/dark cycle in a temperature-controlled room with standard chow and tap water ad libitum.…”
Section: Maternal Hypoxia-induced Iugr Mouse Model and Treatmentmentioning
confidence: 99%
“…23,24 In our previous studies, we have discovered an anti-inflammatory effect of SP against LPS-induced lung injury 25 and the protective role of propionate against LPSinduced bronchopulmonary dysplasia. 26 There is accumulating clinical and experimental evidence that IUGR is a major risk factor for bronchopulmonary dysplasia. 6 In an isocyclic gestational protein restriction-induced IUGR model, propionate concentration was decreased by IUGR before weaning, whereas the concentrations of other SCFAs were decreased at day 40.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple evidences suggested that SIRT1 was activated by SCFAs directly or indirectly ( Jiao et al, 2020 ). In addition, specific SCFAs (such as BA and PA) are activators of the Keap1-Nrf2 defense pathway, which can activate cellular antioxidant mechanisms and downregulate the expression of pro-inflammatory factors ( Guo et al, 2020 ; Chen et al, 2021 ; González-Bosch et al, 2021 ). It is evident that SCFAs could link the microbiota with the maintenance of host redox homeostasis via SIRT1/Nrf2 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the evidence showed that acetate effectively resolved neutrophilic inflammation via inducing caspase-dependent apoptosis of neutrophils, decreasing the activity of nuclear factor-kappa B (NF-κB) and enhancing the production of anti-inflammatory mediators, such as IL-10, transforming growth factor-β (TGF-β), and annexin A1 [ 22 ]. In the LPS-treated neonatal mice model, pulmonary inflammation and oxidative stress were reduced by sodium propionate; in the LPS-treated human pulmonary microvascular endothelial cells (HPMECs) model, sodium propionate not only accelerated Nrf2 nuclear translocation, protected cells, and promoted angiogenesis, but also reduced inflammatory response via the NF-κB pathway [ 23 ]. Moreover, one in vivo study showed that propionate interfered with the production and migration of inflammatory mediators [ 24 ].…”
Section: The Bioactivities Of Scfasmentioning
confidence: 99%